2019
DOI: 10.1111/cei.13271
|View full text |Cite
|
Sign up to set email alerts
|

Tumour necrosis factor α augments the inhibitory effects of CTLA-4-Ig on osteoclast generation from human monocytes via induction of CD80 expression

Abstract: Cytotoxic T lymphocyte antigen-4-immunoglobulin (CTLA-4-Ig) exerts anti-rheumatic action via negative regulation of the co-stimulation process between antigen-presenting cells and T cells. CTLA-4-Ig also binds to CD80/CD86 on monocytes of osteoclast precursors. However, little is known about the effect of CTLA-4-Ig on osteoclastogenesis in rheumatoid arthritis (RA). In this study we evaluated the effects of CTLA-4-Ig on osteoclast generation from human blood monocytes (PBM) and rheumatoid synovial fluid monocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…And osteoblasts are the important functional cells for bone formation, which is involved in early osteogenesis and late bone reconstruction (3). Lipopolysaccharide (LPS) produced by dead bacteria and its inducing inflammatory cytokines (4), such as tumor necrosis factor-a (TNF-a) and interleukin-1 play a significant role in alveolar bone resorption, and they can increase osteoclasts production and promote osteoblast apoptosis (5,6). Studies have shown that LPS could affect the proliferation and apoptosis of osteoblasts through multiple signaling pathways transductions, such as the induction of proliferation through Notch pathway, the inhibition of apoptosis through JNK signaling pathway (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…And osteoblasts are the important functional cells for bone formation, which is involved in early osteogenesis and late bone reconstruction (3). Lipopolysaccharide (LPS) produced by dead bacteria and its inducing inflammatory cytokines (4), such as tumor necrosis factor-a (TNF-a) and interleukin-1 play a significant role in alveolar bone resorption, and they can increase osteoclasts production and promote osteoblast apoptosis (5,6). Studies have shown that LPS could affect the proliferation and apoptosis of osteoblasts through multiple signaling pathways transductions, such as the induction of proliferation through Notch pathway, the inhibition of apoptosis through JNK signaling pathway (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it has been recently reported that abatacept exerts a pharmacologic effect directly on monocytes/macrophages and osteoclasts via CD80/86 in a T cell-independent manner [ 10 ]. For example, abatacept directly inhibits osteoclastogenesis by suppressing the differentiation of circulating osteoclast precursors into functional osteoclasts, and this process is mediated by receptor activator of NF-κB ligand expressed by osteoblasts or activated T cells [ 12 , 13 ]. In addition, short-term coculture of synovial macrophages derived from RA patients and Jurkat cells showed that abatacept suppressed in vitro production of inflammatory cytokines, such as interleukin (IL)-6 and tumor necrosis factor (TNF)-α [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Fc region of CTLA-4-Ig has been modified to reduce its potential to induce complement-dependent and antibody-dependent cellular cytotoxicity 5 . CTLA-4-Ig treatment has several biological functions, including the suppression of monocyte migration 6 and the inhibition of osteoclast differentiation 7 . Persistently activated autoreactive memory B cells have been associated with the development of RA 8 .…”
Section: Introductionmentioning
confidence: 99%